The Study of Workplace Spirituality Effect on Employee Perception of Servant Leadership (پژوهش‌های مدیریت عمومی, 2013)
The paper aim to study the impact of 3 dimensions of workplace spirituality (meaningful work, sense of community and Alignment with the Organization’s Values) on employees perception of servant leadership constituents (service, humility, trusty and love). Using exploratory and confirmative factor analysis a scale is built for measuring workplace spirtuality and servant leadership is measured applying (Gholipour et al ,1388)scales and questionnaire. Then in a metrical research,126 questionnaires were collected and Pearson correlation coefficient, Structural Equation, Friedman analysis and t- test is applied for data analysis. Results show significant relationship between employee in workplace spirituality and perception of leaders in servant leadership. Therefore betterment of work spirtuality will form and foster leaders servant values.